Multi-Village Pooling Project in Indonesia : Handbook for Community-Based Water Supply Organizations - World Bank (Washington, DC, 2014)
The book discusses basic concepts on key topics to managing a small piped water system ideally for up to 1,000 households. It presents tools that can be adapted by Community-Based Water Organizations (CBOs) for use in their operations, such as forms, checklists and procedural guidelines. Illustrative examples have also been compiled from the experiences of the district local governments, support organizations and CBOs operating in East and West Java, who participated in the Multi-Village Pooling (MVP) Project. This toolkit seeks to compile a set of ready resources for organizations supporting Indonesian CBOs and CBOs themselves, which was not previously available despite many years of rural water investment projects. The book introduces fundamental concepts in an easy to-understand way, so that a number of discussions have been simplified. This will give users a basic understanding enough to seek further resources or references or advice from experts, which is encouraged.